Genetic structure in a tropical lek-breeding bird, the blue manakin (Chiroxiphia caudata) in the Brazilian Atlantic Forest - Francisco, Mercival R.; Gibbs, H. Lisle; Galetti, Mauro; Lunardi, Vitor O.; Galetti, Pedro M. (Blackwell Publishing, 2007)
Determining the genetic structure of tropical bird populations is important for assessing potential genetic effects of future habitat fragmentation and for testing hypotheses about evolutionary mechanisms promoting diversification. Here we used 10 microsatellite DNA loci to describe levels of genetic differentiation for five populations of the lek-mating blue manakin (Chiroxiphia caudata), sampled along a 414-km transect within the largest remaining continuous tract of the highly endangered Atlantic Forest habitat in southeast Brazil. We found small but significant levels of differentiation between most populations. F-ST values varied from 0.0 to 0.023 (overall F-ST = 0.012) that conformed to a strong isolation by distance relationship, suggesting that observed levels of differentiation are a result of migration-drift equilibrium. N(e)m values estimated using a coalescent-based method were small (<= 2 migrants per generation) and close to the minimum level required to maintain genetic similarity between populations. An implication of these results is that if future habitat fragmentation reduces dispersal between populations to even a small extent, then individual populations may undergo a loss of genetic diversity due to an increase in the relative importance of drift, since inbreeding effective population sizes are relatively small (N-e similar to 1000). Our findings also demonstrate that population structuring can occur in a tropical bird in continuous habitat in the absence of geographical barriers possibly due to behavioural features of the species.
Keywords: effective population size; gene flow; microsatellite DNA; neotropical passerine birds; pipridae